Material for producing low-carbon high-molybdenum stainless steel pipeline and preparation method thereof
By optimizing chemical composition and preparation process in low-carbon high-molybdenum stainless steel pipelines, especially controlling the dissolution of molybdenum elements through solid solution treatment, the problem of molybdenum segregation during material preparation is solved, and the corrosion resistance and high-temperature performance of the material are improved.
Patent Information
- Application Number
- CN202510161037.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-13
- Publication Date
- 2025-03-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
After the existing low-carbon high-molybdenum stainless steel pipelines increase the molybdenum content, it is difficult to prepare the material, resulting in the growth of grains, which may form a brittle phase such as σ phase, reducing the toughness, plasticity and corrosion resistance of the material.
Low-carbon high-molybdenum stainless steel materials are used, and the chemical compositions include 0.01-0.02% carbon, 20.0-22.5% chromium, 15.0-18.5% nickel, and 5.5-8.8% molybdenum. The temperature, time and cooling process are controlled through solid solution treatment to reduce the molybdenum segregation effect, ensure that the alloying elements are fully dissolved in the austenite matrix, and inhibit the precipitation of other phases.
The corrosion resistance, high temperature strength and creep resistance of low-carbon high-molybdenum stainless steel pipes are improved, and the toughness and plasticity of the material are reduced and the corrosion resistance is reduced.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of metal material preparation, and specifically relates to a material for producing low-carbon high-molybdenum stainless steel pipes and a preparation method thereof. Background Art
[0002] Stainless steel refers to steel that is resistant to corrosion by weakly corrosive media such as air, steam, and water, and chemically corrosive media such as acids, alkalis, and salts. The corrosion resistance of stainless steel depends on the alloying elements contained in the steel. The basic alloying elements of stainless steel include nickel, molybdenum, nitrogen, etc., to meet the requirements of stainless steel structure and performance for various uses. Stainless steel is easily corroded by chloride ions because chromium, nickel, and chlorine are isotopic elements, and isotopic elements will interchange and assimilate to form stainless steel corrosion. In addition, the strength of stainless steel is also very high, so it is widely used in transportation pipelines, that is, stainless steel pipelines.
[0003] Traditional stainless steel pipes are usually martensitic or ferritic stainless steel, which are low in cost and have good corrosion resistance. However, in special environments, especially those containing chlorides, traditional ordinary stainless steel pipes are not very suitable. At this time, austenitic stainless steel, specifically a low-carbon high-molybdenum stainless steel pipe, is needed. Low-carbon high-molybdenum stainless steel pipes have excellent corrosion resistance and good resistance to various environments, especially in environments containing chlorides. Their comprehensive properties such as strength, toughness, formability and weldability are very good, and they have good resistance to high and low temperatures, that is, they can be used at higher temperatures without hardening, and they also maintain good toughness at low temperatures.
[0004] The molybdenum content in existing low-carbon, high-molybdenum stainless steel is about 4-5%, and the combined effect of chromium Cr and molybdenum Mo can improve the corrosion resistance of steel in reducing media. Therefore, in order to obtain low-carbon, high-molybdenum stainless steel with better corrosion resistance, it is necessary to increase the molybdenum Mo content in low-carbon, high-molybdenum stainless steel. However, when the molybdenum content in low-carbon, high-molybdenum stainless steel increases, it will make the material difficult to prepare; that is, when low-carbon, high-molybdenum stainless steel is prepared by existing stainless steel technology, due to the segregation trend of molybdenum, the high molybdenum content of low-carbon, high-molybdenum stainless steel will affect the grain growth behavior of stainless steel. In some cases, low-carbon, high-molybdenum stainless steel will even form special phases, such as hard and brittle σ phases, which ultimately lead to a decrease in the material's toughness and plasticity and a decrease in corrosion resistance. Summary of the invention
[0005] The present invention provides a material for producing a low-carbon high-molybdenum stainless steel pipeline and a preparation method thereof, which are used to solve the technical problems raised in the above background technology.
[0006] The technical solution adopted by the present invention is: a material for producing a low-carbon high-molybdenum stainless steel pipe, wherein the low-carbon high-molybdenum stainless steel pipe is made of a low-carbon high-molybdenum stainless steel material; the low-carbon high-molybdenum stainless steel material comprises the following chemical element components in weight percentage: Carbon (C) 0.01-0.02%, chromium (Cr) 20.0-22.5%, nickel (Ni) 15.0-18.5%, molybdenum (Mo) 5.5-8.8%, manganese (Mn) 0.9-1.4%, silicon (Si) ≤1%, phosphorus (P) ≤0.02%, sulfur (S) ≤0.01%, nitrogen (N) 0.2-0.3%, the balance is iron (Fe); Among them, in the low-carbon high-molybdenum stainless steel material, the weight proportion of molybdenum (Mo) depends on the amount of chromium (Cr), that is, when the amount of chromium (Cr) is at the upper limit, the amount of molybdenum (Mo) is also at the upper limit, otherwise it is at the lower limit.
[0007] A method for preparing a material for producing a low-carbon high-molybdenum stainless steel pipe comprises the following steps: Step (1) raw material preparation; Step (2) smelting; Step (3) refining; Step (4) casting; Step (5) intermediate heat treatment; Step (6) final heat treatment; Step (7) cold working; The raw materials include: pig iron, scrap iron, ferrochrome, ferronickel, ferromolybdenum and ferromanganese; The intermediate heat treatment includes solution treatment of the material obtained by casting; the minimum solution treatment temperature is: 900°C+2×% (nickel Ni content)+20×% (molybdenum Mo content), the maximum solution treatment temperature is: 1000°C+2×% (nickel Ni content)+20×% (molybdenum Mo content), the holding time is 8h, and rapid cooling is performed after the holding is completed; Wherein, the temperature of the final heat treatment is: 850-950°C, and the treatment time of the final heat treatment is 1-2h.
[0008] As a preferred solution of the present invention, the chemical elements titanium (Ti) and niobium (Nb) are further added to the low-carbon high-molybdenum stainless steel material, and their weight percentages are respectively: titanium (Ti) 0.005-0.01%, niobium (Nb) 0.004-0.008%.
[0009] As a preferred embodiment of the present invention, the low-carbon high-molybdenum stainless steel material includes the following chemical element components in weight percentage: carbon (C) 0.015%, chromium (Cr) 21.5%, nickel (Ni) 18.0%, molybdenum (Mo) 8.5%, manganese (Mn) 0.95%, silicon (Si) 0.84%, phosphorus (P) 0.012%, sulfur (S) 0.007%, nitrogen (N) 0.24%, titanium (Ti) 0.005%, niobium (Nb) 0.004%, and the balance is iron (Fe).
[0010] As a preferred solution of the present invention, the intermediate heat treatment further includes material property monitoring, and the material is subjected to cyclic solution treatment according to the monitoring results.
[0011] As a preferred embodiment of the present invention, when performing cyclic solution treatment, the material is tempered after each solution treatment, the tempering temperature is 500-650°C, and the tempering time is 1-1.5h.
[0012] As a preferred solution of the present invention, the material performance monitoring comprises the following steps: S1 sampling, that is, sampling the material after each solution treatment; S2 test, hardness test, metallographic analysis, mechanical property test and corrosion resistance test are carried out on the samples obtained; S3 analysis compares the test results with the required standards to determine whether cyclic solution treatment is still needed.
[0013] As a preferred embodiment of the present invention, the raw materials are preheated before smelting in step (2).
[0014] As a preferred solution of the present invention, during the smelting process, ferromolybdenum and ferrochromium are firstly loaded into the furnace body, and ferronickel and ferromanganese are then loaded into the furnace body, and a decarburizer is added to the melt.
[0015] As a preferred embodiment of the present invention, in the refining of step (3), the refining equipment adopts a vacuum furnace, which provides a vacuum refining environment and stirs the melt during the refining process.
[0016] Compared with the prior art, the present invention has the following beneficial effects: The invention discloses a low-carbon high-molybdenum stainless steel material with a molybdenum (Mo) content of more than 5% for producing a low-carbon high-molybdenum stainless steel pipe, which has better corrosion resistance, high-temperature strength and creep resistance; at the same time, when preparing the low-carbon high-molybdenum stainless steel material, the temperature, time and cooling of the material are controlled by solid solution treatment, so that the influence of molybdenum segregation is reduced during the preparation of the low-carbon high-molybdenum stainless steel, the alloy elements are fully dissolved in the austenite matrix, and the alloy elements are kept supersaturated in the austenite, thereby inhibiting the precipitation of other phases, and will not cause a decrease in the toughness and plasticity of the material and a decrease in corrosion resistance. DETAILED DESCRIPTION
[0017] In order to enable those skilled in the art to better understand the technical solution, the technical solution is described in detail below in conjunction with the embodiments. The description in this section is only exemplary and explanatory and should not have any limiting effect on the scope of protection of the present application. Embodiment 1:
[0018] A material for producing a low-carbon high-molybdenum stainless steel pipe, wherein the low-carbon high-molybdenum stainless steel pipe is made of a low-carbon high-molybdenum stainless steel material; the low-carbon high-molybdenum stainless steel material comprises the following chemical element components in weight percentage: Carbon (C) 0.01-0.02%, chromium (Cr) 20.0-22.5%, nickel (Ni) 15.0-18.5%, molybdenum (Mo) 5.5-8.8%, manganese (Mn) 0.9-1.4%, silicon (Si) ≤1%, phosphorus (P) ≤0.02%, sulfur (S) ≤0.01%, nitrogen (N) 0.2-0.3%, the balance is iron (Fe); Among them, in the low-carbon high-molybdenum stainless steel material, the weight proportion of molybdenum (Mo) depends on the amount of chromium (Cr), that is, when the amount of chromium (Cr) is at the upper limit, the amount of molybdenum (Mo) is also at the upper limit, otherwise it is at the lower limit.
[0019] Furthermore, the chemical elements titanium (Ti) and niobium (Nb) are added to the low-carbon high-molybdenum stainless steel material, and their weight percentages are respectively: titanium (Ti) 0.005-0.01%, niobium (Nb) 0.004-0.008%; titanium (Ti) and niobium (Nb) are added as stabilizing elements to form titanium carbide or niobium carbide to reduce the formation of chromium carbide.
[0020] Furthermore, the low-carbon, high-molybdenum stainless steel material includes the following chemical element components in weight percentage: carbon (C) 0.015%, chromium (Cr) 21.5%, nickel (Ni) 18.0%, molybdenum (Mo) 8.5%, manganese (Mn) 0.95%, silicon (Si) 0.84%, phosphorus (P) 0.012%, sulfur (S) 0.007%, nitrogen (N) 0.24%, titanium (Ti) 0.005%, niobium (Nb) 0.004%, and the balance is iron (Fe).
[0021] Two comparative examples are added in this embodiment, namely, comparative example 1 and comparative example 2; Comparative Example 1 includes the following chemical element compositions in weight percentage: carbon (C) 0.06%, chromium (Cr) 18.0%, nickel (Ni) 8.0%, manganese (Mn) 1.9%, silicon (Si) 0.7%, phosphorus (P) 0.045%, sulfur (S) 0.03%, and the balance is iron (Fe); that is, Comparative Example 1 is 304 stainless steel.
[0022] Comparative Example 2 includes the following chemical element compositions in weight percentage: carbon (C) 0.02%, chromium (Cr) 16.3%, nickel (Ni) 10.3%, molybdenum (Mo) 2.4%, manganese (Mn) 1.7%, silicon (Si) 0.5%, phosphorus (P) 0.04%, sulfur (S) 0.01%, titanium (Ti) + niobium (Nb) 0.15%, and the balance is iron (Fe); that is, Comparative Example 2 is 316L stainless steel.
[0023] The present embodiment 1, comparative example 1 and comparative example 2 were tested, and the test results were compared in a table as shown in Table 1 below:
[0024] Table 1 According to the test results, a low-carbon, high-molybdenum stainless steel material with a molybdenum (Mo) content of 8.5% used in the production of low-carbon, high-molybdenum stainless steel pipes has better corrosion resistance, high-temperature strength and creep resistance. Embodiment 2:
[0025] A method for preparing a material for producing a low-carbon high-molybdenum stainless steel pipe comprises the following steps: Step (1) raw material preparation; that is, selecting suitable raw materials, and the purity of the alloying elements such as iron, chromium, nickel, molybdenum, etc. used meets the requirements of material preparation; then the ingredients are mixed according to the target material component ratio to ensure that the preparation requirements are met.
[0026] Step (2) smelting: before the raw materials are loaded into the furnace body, they are preheated and then smelted. The prepared raw materials are loaded into the furnace body and the furnace body is turned on for heating. During this process, ferromolybdenum and ferrochromium are first loaded into the furnace body, and ferronickel and ferromanganese are loaded into the furnace body later. The charge is heated to a molten state, wherein iron melts first, followed by other alloying elements. During the melting process, a decarburizing agent (such as ferrosilicon) is added to reduce the carbon content.
[0027] Specifically, preheating is used to reduce the temperature gradient during the raw material smelting process to avoid overheating of the melt; high-melting point alloy elements such as chromium and molybdenum are added first, and then low-melting point metals such as iron and nickel are added, which can more effectively control the smelting temperature; using a decarburizer instead of oxygen blowing decarburization can avoid the formation of oxides of elements such as molybdenum in the melt.
[0028] Step (3) refining: after smelting, the melt is sampled and analyzed according to its chemical composition, and corresponding refining adjustments are made according to the analysis results; the refining equipment adopts a vacuum furnace, which provides a vacuum refining environment to remove gases such as oxygen, nitrogen and hydrogen. The refining temperature is controlled between 1650°C and 1800°C, and argon is used to stir the melt to promote uniform composition and remove non-metallic inclusions.
[0029] Specifically, refining improves the purity of the melt, removes gases and impurities in the melt, and ensures that the quality of the final material meets the requirements.
[0030] Step (4) casting: before casting, a covering agent (such as glass powder, borax, etc.) is added to the surface of the molten pool to isolate the air and reduce oxidation, and then the melt is quickly poured to reduce oxidation and inclusions; Step (5) intermediate heat treatment; the intermediate heat treatment comprises performing a solution treatment on the material obtained by casting; the minimum solution treatment temperature is: 900°C + 2×% (nickel Ni content) + 20×% (molybdenum Mo content), the maximum solution treatment temperature is: 1000°C + 2×% (nickel Ni content) + 20×% (molybdenum Mo content), the holding time is 8h, and rapid water cooling is performed after the holding is completed; the temperature, time and cooling of the material are controlled by the solution treatment, so that the influence of molybdenum segregation on the low-carbon high-molybdenum stainless steel is reduced during the preparation process, the alloy elements are fully dissolved in the austenite matrix, and the alloy elements are kept supersaturated in the austenite, thereby inhibiting the precipitation of other phases, and will not cause the material to reduce its toughness and plasticity during the preparation process and reduce its corrosion resistance.
[0031] The intermediate heat treatment also includes material property monitoring, and the material is subjected to cyclic solution treatment according to the monitoring results, including the following steps: S1 sampling, that is, sampling the material after each solution treatment; S2 test, hardness test, metallographic analysis, mechanical property test and corrosion resistance test are carried out on the samples obtained; S3 analysis compares the test results with the required standards to determine whether cyclic solution treatment is still needed.
[0032] During the cyclic solution treatment, the material should be tempered after each solution treatment, with the tempering temperature being 500-650°C and the tempering time being 1-1.5h. Tempering can eliminate the residual stress of the material after solution treatment, increase the toughness of the material, and stabilize the organizational structure of the material.
[0033] Specifically, the cyclic solution treatment combined with tempering in the intermediate heat treatment step can achieve a good balance of strength, plasticity and toughness, and improve the corrosion resistance and stability of the material. The cyclic solution treatment helps to reduce the precipitation phase, and the tempering treatment helps to prevent the formation of new precipitation phases, thereby maintaining the material properties. Tempering after solution treatment can control the growth of grains and maintain a fine grain size, which is beneficial to improving the comprehensive performance of the material, and the material will show better processing performance in the subsequent cold working process.
[0034] Step (6) final heat treatment: The temperature of the final heat treatment is 850-950°C, and the treatment time of the final heat treatment is 1-2 hours. The final heat preservation promotes the formation of carbides beneficial to the material, which helps to further improve the material performance.
[0035] Step (7) cold working; including cold rolling: rolling the material at room temperature to achieve higher dimensional accuracy and surface finish. Embodiment 3:
[0036] The low-carbon high-molybdenum stainless steel material of Example 1 is used as the preparation and processing standard, which specifically includes the following chemical element components in weight percentage: carbon (C) 0.015%, chromium (Cr) 21.5%, nickel (Ni) 18.0%, molybdenum (Mo) 8.5%, manganese (Mn) 0.95%, silicon (Si) 0.84%, phosphorus (P) 0.012%, sulfur (S) 0.007%, nitrogen (N) 0.24%, titanium (Ti) 0.005%, niobium (Nb) 0.004%, and the balance is iron (Fe); in this embodiment, the preparation of the low-carbon high-molybdenum stainless steel material is divided into the following steps: Step (1) Raw material preparation: Select alloy elements such as iron, chromium, nickel, and molybdenum, with a purity requirement of 99.5%. Prepare the ingredients according to the required standard element composition to ensure the accuracy of the composition.
[0037] Step (2) smelting: preheat the raw materials prepared in step (1) to 400°C, then load them into a vacuum furnace, start the furnace body, begin heating to 1000°C, load ferrochrome and ferromolybdenum, then load ferronickel and ferromanganese, gradually increase the furnace temperature to 1550°C during the process, melt the raw materials in the furnace at high temperature, and add ferrosilicon as a decarburizer.
[0038] Step (3) refining: Before refining, the melt was sampled and analyzed, the vacuum refining temperature was controlled at 1750°C, argon was used for stirring, and the refining time was 50 minutes to ensure the purity of the melt.
[0039] Step (4) Casting: After refining, a glass powder covering agent is added to the surface of the molten pool, and then the melt is quickly poured into a casting mold and allowed to cool and solidify.
[0040] Step (5) Intermediate heat treatment: The solution treatment temperature is set to 1150°C (900°C + 2×18%Ni + 20×8.5%Mo=1106°C<1150°C<1206°C=1000°C + 2×18%Ni + 20×8.5%Mo), and the solution treatment is maintained for 8 hours before rapid water cooling. The solution treated material is then monitored, i.e., the following steps are performed: S1 sampling, i.e. sampling the material after the solution treatment; S2 test: the samples obtained this time (named as sample 1, sample 2, etc.) are subjected to hardness test, metallographic analysis, mechanical property test and corrosion resistance test; S3 analysis compares the test results with the required standards to determine whether cyclic solution treatment is still needed.
[0041] In this embodiment, the specific monitoring results and the judgment of the number of cycles are tabulated, as shown in Table 2 below: That is, as shown in the table, three cycles of solution treatment were carried out, and tempering treatment was carried out after each solution treatment, with the tempering temperature being 650°C and the time being 1.5 hours.
[0042] Table 2 Step (6) Final heat treatment: The final heat treatment temperature is 950°C and the insulation time is 2 hours.
[0043] Step (7) cold working: cold rolling the obtained material as required to obtain the final material. Embodiment 4:
[0044] In this embodiment, a low-carbon high-molybdenum stainless steel material is prepared, which specifically includes the following chemical element components in weight percentage: carbon (C) 0.02%, chromium (Cr) 20.3%, nickel (Ni) 15.5%, molybdenum (Mo) 7.0%, manganese (Mn) 1.0%, silicon (Si) 0.92%, phosphorus (P) 0.015%, sulfur (S) 0.009%, nitrogen (N) 0.2%, titanium (Ti) 0.01%, niobium (Nb) 0.008%, and the balance is iron (Fe); divided into the following steps: Step (1) Raw material preparation: Select alloy elements such as iron, chromium, nickel, and molybdenum, with a purity requirement of 99.0%. Prepare the ingredients according to the required standard element composition to ensure the accuracy of the composition.
[0045] Step (2) smelting: preheat the raw materials prepared in step (1) to 400°C, then load them into a vacuum furnace, start the furnace body, begin heating to 1000°C, load ferrochrome and ferromolybdenum, then load ferronickel and ferromanganese, gradually increase the furnace temperature to 1550°C during the process, melt the raw materials in the furnace at high temperature, and add ferrosilicon as a decarburizer.
[0046] Step (3) refining: Before refining, the melt was sampled and analyzed, the vacuum refining temperature was controlled at 1700°C, argon was used for stirring, and the refining time was 40 minutes to ensure the purity of the melt.
[0047] Step (4) Casting: After refining, a glass powder covering agent is added to the surface of the molten pool, and then the melt is quickly poured into a casting mold and allowed to cool and solidify.
[0048] Step (5) Intermediate heat treatment: The solution treatment temperature is set to 1100°C (900°C + 2×15.5%Ni + 20×7.0%Mo = 1071°C < 1200°C < 1171°C = 1000°C + 2×15.5%Ni + 20×7.0%Mo), and the solution treatment is kept for 8 hours and then rapidly cooled with water. The solution treated material is then monitored, i.e., the following steps are performed: S1 sampling, i.e. sampling the material after the solution treatment; S2 test: hardness test, metallographic analysis, mechanical property test and corrosion resistance test are performed on the samples obtained this time (named as sample A, sample B, etc.); S3 analysis compares the test results with the required standards to determine whether cyclic solution treatment is still needed.
[0049] In this embodiment, the specific monitoring results and the judgment of the number of cycles are tabulated, as shown in Table 2 below: That is, as shown in the table, two cycles of solution treatment were carried out, and tempering treatment was carried out after each solution treatment, with the tempering temperature being 650°C and the time being 1.5 hours.
[0050] Table 3 Step (6) Final heat treatment: The final heat treatment temperature is 850°C and the holding time is 1 hour to promote carbide formation.
[0051] Step (7) cold working; including cold rolling: rolling the material at room temperature to achieve higher dimensional accuracy and surface finish.
[0052] According to all the above embodiments, the present invention discloses a low-carbon high-molybdenum stainless steel material for producing low-carbon high-molybdenum stainless steel pipes, wherein the content of molybdenum (Mo) exceeds 5%, and the material has better corrosion resistance, high temperature strength and creep resistance; at the same time, when preparing the low-carbon high-molybdenum stainless steel material, the temperature, time and cooling of the material are controlled by solid solution treatment, so that the influence of molybdenum segregation is reduced during the preparation process of the low-carbon high-molybdenum stainless steel, the alloy elements are fully dissolved in the austenite matrix, and the alloy elements are kept supersaturated in the austenite, thereby inhibiting the precipitation of other phases, and will not lead to a decrease in the toughness and plasticity of the material and a decrease in corrosion resistance; in the intermediate heat treatment step, cyclic solid solution treatment is combined with tempering, and the two treatment methods are combined to obtain a good balance of strength, plasticity and toughness, and improve the corrosion resistance and stability of the material. The cyclic solid solution treatment helps to reduce the precipitation phase, and the tempering treatment helps to prevent the formation of new precipitation phases, thereby maintaining the material performance. Tempering after solid solution treatment can control the growth of grains and maintain a fine grain size, which is beneficial to improving the comprehensive performance of the material, and the material will show better processing performance in the subsequent cold working process.
[0053] It should be noted that, in this article, the terms "include", "comprises" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. Specific examples are used in this article to illustrate the principles and implementation methods of the technical solution of the present application. The above examples are only used to help understand the method of the present application and its core idea. The above is only a preferred implementation method of the present application. It should be pointed out that due to the limitations of textual expression and the objective existence of infinite specific structures, for ordinary technicians in this technical field, without departing from the principles of the present application, several improvements, modifications or changes can be made, and the above technical features can also be combined in an appropriate manner; these improvements, modifications, changes or combinations, or the direct application of the patent concept and technical solution to other occasions without improvement, should be regarded as the scope of protection of the present application.
Claims
1. A material for producing low-carbon high-molybdenum stainless steel pipes and a preparation method thereof, characterized in that: The low-carbon high-molybdenum stainless steel pipe is made of low-carbon high-molybdenum stainless steel material; the low-carbon high-molybdenum stainless steel material includes the following chemical element components in weight percentage: Carbon (C) 0.01-0.02%, chromium (Cr) 20.0-22.5%, nickel (Ni) 15.0-18.5%, molybdenum (Mo) 5.5-8.8%, manganese (Mn) 0.9-1.4%, silicon (Si) ≤1%, phosphorus (P) ≤0.02%, sulfur (S) ≤0.01%, nitrogen (N) 0.2-0.3%, the balance is iron (Fe); Among them, in the low-carbon high-molybdenum stainless steel material, the weight proportion of molybdenum (Mo) depends on the amount of chromium (Cr), that is, when the amount of chromium (Cr) is at the upper limit, the amount of molybdenum (Mo) is also at the upper limit, otherwise it is at the lower limit; The preparation method of the material comprises the following steps: Step (1) raw material preparation; Step (2) smelting; Step (3) refining; Step (4) casting; Step (5) intermediate heat treatment; Step (6) final heat treatment; Step (7) cold working; The raw materials include: pig iron, scrap iron, ferrochrome, ferronickel, ferromolybdenum and ferromanganese; The intermediate heat treatment includes solution treatment of the material obtained by casting; the minimum solution treatment temperature is: 900°C + 2× nickel content + 20× molybdenum content, the maximum solution treatment temperature is: 1000°C + 2× nickel content + 20× molybdenum content, the holding time is 8h, and rapid cooling is performed after the holding is completed; Wherein, the temperature of the final heat treatment is: 850-950°C, and the treatment time of the final heat treatment is 1-2h; The intermediate heat treatment also includes material property monitoring, and cyclic solution treatment of the material is performed according to the monitoring results; When performing cyclic solution treatment, the material must be tempered after each solution treatment. The tempering temperature is 500-650°C and the tempering time is 1-1.5h.
2. A material for producing low-carbon high-molybdenum stainless steel pipes and a preparation method thereof according to claim 1, characterized in that: The low-carbon high-molybdenum stainless steel material also contains chemical elements titanium (Ti) and niobium (Nb), and the weight percentages thereof are respectively: titanium (Ti) 0.005-0.01%, and niobium (Nb) 0.004-0.008%.
3. A material for producing low-carbon high-molybdenum stainless steel pipes and a preparation method thereof according to claim 2, characterized in that: The low-carbon, high-molybdenum stainless steel material includes the following chemical element components in weight percentage: carbon (C) 0.015%, chromium (Cr) 21.5%, nickel (Ni) 18.0%, molybdenum (Mo) 8.5%, manganese (Mn) 0.95%, silicon (Si) 0.84%, phosphorus (P) 0.012%, sulfur (S) 0.007%, nitrogen (N) 0.24%, titanium (Ti) 0.005%, niobium (Nb) 0.004%, and the balance is iron (Fe).
4. A material for producing low-carbon high-molybdenum stainless steel pipes and a preparation method thereof according to claim 1, characterized in that: The material performance monitoring comprises the following steps: S1 sampling, that is, sampling the material after each solution treatment; S2 test, hardness test, metallographic analysis, mechanical property test and corrosion resistance test are carried out on the samples obtained; S3 analysis compares the test results with the required standards to determine whether cyclic solution treatment is still needed.
5. The material for producing low-carbon high-molybdenum stainless steel pipes and the preparation method thereof according to claim 1, characterized in that: The raw materials must be preheated before smelting in step (2).
6. A material for producing low-carbon high-molybdenum stainless steel pipes and a preparation method thereof according to claim 5, characterized in that: During the smelting process, ferromolybdenum and ferrochromium are firstly loaded into the furnace body, and ferronickel and ferromanganese are then loaded into the furnace body, and a decarburizing agent is added to the melt.
7. The material for producing low-carbon high-molybdenum stainless steel pipes and the preparation method thereof according to claim 1, characterized in that: In the refining of step (3), the refining equipment adopts a vacuum furnace, which provides a vacuum refining environment and stirs the melt during the refining process.
Citation Information
Patent Citations
Austenite-based thick stainless-steel plate and production method therefor
CN110520549A
Stainless steel tube and method for manufacturing same
CN115151670A
Stainless steel tube and method for manufacturing same
CN115176043A
Duplex stainless steel tube and method for manufacturing same
CN116917523A